1995
DOI: 10.1136/bmj.311.7011.981
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of laparoscopic versus open repair of inguinal hernia: early results

Abstract: Objective-To establish the safety, short term outcome, and theatre costs of transabdominal laparoscopic repair of inguinal hernia performed as day surgery.Design-Randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(82 citation statements)
references
References 10 publications
5
72
1
4
Order By: Relevance
“…However at 3 months of follow up, there was no difference in the activity level between the laparoscopic and open group. Lawrence et al 18 did not find any significant difference in return to normal activities in two groups.…”
Section: Time To Return To Normal Activitymentioning
confidence: 82%
“…However at 3 months of follow up, there was no difference in the activity level between the laparoscopic and open group. Lawrence et al 18 did not find any significant difference in return to normal activities in two groups.…”
Section: Time To Return To Normal Activitymentioning
confidence: 82%
“…Therefore, a definitive conclusion on the cost-effectiveness of OPPR may not be inferred from this study. However, there are several studies which reported the cost-effectiveness of laparoscopic inguinal hernia repair compared to conventional open repair [42][43][44]. The estimated cost of LPPR is US$1250 compared to US$600 for OPPR.…”
Section: Discussionmentioning
confidence: 99%
“…Although we know the difficulty of measuring postoperative pain due to its subjective nature, we used two methods to quantify it: the numerical scale of pain and the patient's need for rescue analgesia 1,6,8,11,12,14,15,19 . Although there was no difference between the groups regarding the pain scale, with 97.5% of the patients reporting mild to moderate pain and only one patient with severe pain in both groups, we noticed that the patients in the SF group requested more doses of analgesics than in the VL group, although this fact is also devoid of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances have also allowed the development of different types of surgical mesh, such as with resorbable material, self-fixating adhesives, low weight and fixation with fibrin glue 3,11,12 . This large arsenal of available material, associated with a wide variety of techniques (open or laparoscopic), raises questions about the gold standard for the treatment of inguinal hernia.…”
mentioning
confidence: 99%